ABSTINENCE COMMUNICATION CAMPAIGNS AND PREVENTION OF HIV AND AIDS AMONG UNDERGRADUATE UNIVERSITY STUDENTS IN KENYA: A CASE OF JOMO KENYATTA UNIVERSITY OF AGRICULTURE AND TECHNOLOGY - Kyalo, Daniel; Mberia, Hellen (International Journal of Communication and Public Relation, 2022)
Purpose: The study sought to establish the influence of abstinence communication campaigns on prevention of HIV and AIDS among undergraduate university students in Kenya. Materials and Methods: The study employs a descriptive research design, with the focus on undergraduate students from all the seventy-four universities. Sample size determination was done as follows where the Fisher's formula was used to select an appropriate sample from the populated to be targeted. The study thus, targeted 384 undergraduate students. In order to avoid biased results, the study excluded the respondents who participated in the pilot study. The study used qualitative as well as quantitative which prior to analysis, was sorted to ensure completeness. Quantitative data was collected using three hundred and eighty-four semi-structured questionnaires. On the other hand, qualitative data was collected by use of seven Key Informant Interview (KII) guides. Coding of the responses was done, in order to enable the data to be recorded into SPSS software. The quantitative information was investigated descriptively and inferential statistics were drawn by the use of Statistical Package for Social Sciences (SPSS variant 21.0). Results were then presented in tables, diagrams and charts. Qualitative data collected from the open-ended part of the questionnaire was analyzed using content analysis and the results were presented in prose form. Results: The findings revealed that medium of delivery and prevention of HIV and AIDS are positively and significantly related (Î²=0.391, p=0.023). Likewise, frequency of abstinence and prevention of HIV and AIDS are positive and statistically related (Î²=0.399, p=0.003). The table further indicates that source of the abstinence campaign messages and prevention of HIV and AIDS are positive and significantly related (Î²=0.351, p=0.001). Upon interacting the stakeholder intervention in the model, it was found to be positively and significantly related as shown by (B=0.033, p=0.009). Unique contribution to theory, practice and policy: The cultivation theory may be used to anchor future studies in abstinence communication campaigns. The study recommended that students in universities are encouraged to get tested and know their status; the university management needs to scale up the awareness strategies to students on the need to practice safe sex to prevent HIV infection for future healthy and capacitated generation; the government through the ministry of health needs to invest in propagating the messages by use of the interactive, student-centered methods of teaching, rather than heavily didactic ones, which has been proven to be more successful.